Effect of Credit Union Governance On Financial Performance: Perspective Analysis of 4-Lever Management Control System - Monica, Monica (Dinasti Publisher, 2024)
In the process of implementing the principles of credit union, credit union certainly focuses on the importance of realizing social and Human Development. (World Council of Credit Union's (WOCCU), 2007). In achieving this goal, the Indonesian credit union is required to implement the provisions of the Ministry of Cooperatives and SMEs on the implementation of Cooperative Health Level examination No. 9 of 2020, the research Model used is an instrumental case study, this is used to make it easier for researchers to review the data on cooperative health examination results for 3 (three) years (Amir H, 2020). For the risk profile indicator, it is good that can be done by CU Madani is to continue to mitigate periodically if the discovery of risks that occur so that the small risk does not become a big risk. Provision of briefing to employees before the service needs to be applied so that events that may have not been resolved yesterday can be discussed and find a solution together.